Effectiveness of counselling and psychotherapeutic interventions for people with dementia and their families: a systematic review. Issue 4 (15th April 2022) - Shoesmith, Emily; Griffiths, Alys Wyn; Sass, Cara; Charura, Divine
Abstract: As there is currently no cure for dementia, providing psycho-social support is imperative. Counselling and psychotherapeutic interventions offer a way to provide individualised support for people with dementia and their families. However, to date, there has not been a systematic review examining the research evidence for these interventions. This review aimed to examine the following research questions: (1) Are counselling/psychotherapeutic interventions effective for people with dementia?, (2) Are counselling/psychotherapeutic interventions effective for care-givers of people with dementia? and (3) Which modes of delivery are most effective for people with dementia and care-givers of people with dementia? A systematic literature search was conducted in MEDLINE (via PubMed), PsycINFO and CINAHL in March 2019. Keyword searches were employed with the terms 'dement*', 'counsel*', 'psychotherapy', 'therap*', 'care' and 'outcome', for the years 2000–2019. Thirty-one papers were included in the review, from seven countries. Twenty studies were randomised controlled trials (RCTs) or adopted a quasi-experimental design. The remaining studies were qualitative or single-group repeated-measures design. The review identified variation in the counselling/psychotherapeutic approaches and mode of delivery. Most interventions adopted either a problem-solving or cognitive behavioural therapy approach. Mixed effectiveness was found on various outcomes. The importance of customised modifications for people with dementia was highlighted consistently. Understanding the dyadic relationships between people with dementia and their care-givers is essential to offering effective interventions and guidance for practitioners is needed. Information about the cognitive impairment experienced by participants with dementia was poorly reported and is essential in the development of this research area. Future studies should consider the impact of cognitive impairment in developing guidance for counselling/psychotherapeutic intervention delivery for people with dementia.